Clinical and epidemiological features of paracoccidioidomycosis due to Paracoccidioides lutzii. - Rosane Christine Hahn; Anderson Messias Rodrigues; Paula Portella Della Terra; Andréia Ferreira Nery; Hugo Dias Hoffmann-Santos; Hellen Meira Góis; Cor Jesus Fernandes Fontes; Zoilo Pires de Camargo (Public Library of Science (PLoS), 2019)
Background The fungus Paracoccidioides lutzii was recently included as a new causative species of paracoccidioidomycosis (PCM) and most cases have been reported from Brazil. According to available epidemiological information, P. lutzii is concentrated in the Middle-West region in Brazil, mainly in the state of Mato Grosso. However, clinical and laboratorial data available on patients infected with P. lutzii remain extremely limited. Methodology/main findings This work describes the clinical manifestations of 34 patients suffering from PCM caused by P. lutzii, treated along 5 years (2011-2017) at a reference service center for systemic mycoses in Mato Grosso, Brazil. Adult rural workers (men), aged between 28 and 67 predominated. All patients had the chronic form of the disease, and the oral mucosa (n = 19; 55.9%), lymph nodes (n = 23; 67.7%), skin (n = 16; 47.1%) and lung (n = 28; 82.4%) were the most affected sites. Alcohol intake (n = 19; 55.9%) and smoking (n = 29; 85.3%) were frequent habits among the patients. No patient suffered from any other life-threatening disease, such as tuberculosis, cancer or other inflammatory or infectious parasitic diseases. The positivity in culture examination (97.1%) was higher than that found for the direct mycological examination (88.2%). Particularly, one patient presented fungemia at diagnosis, which lead to his death. The time elapsed between the initial symptoms and the initiation of treatment of PCM caused by P. lutzii was 19.7 (31.5) months, with most patients diagnosed 7 months after the symptoms' onset. Conclusions/significance Compared with the classical clinical-epidemiological profile of PCM caused by P. brasiliensis, the results of this descriptive study did not show significant clinical or epidemiological differences that could be attributed to the species P. lutzii. Future studies may confirm or refute the existence of clinical differences between the two fungal species.